Experiences of Self-Criticism and Self-Compassion in People Diagnosed With Cancer: A Multimethod Qualitative Study - Austin, Judith; Drossaert, Constance H. C.; Sanderman, Robbert; Schroevers, Maya J.; Bohlmeijer, Ernst T. (Frontiers in Psychology, 2021)
Objective: Self-criticism is a self-condemning and self-compassion a supportive style of self-to-self relating. These concepts have increasingly been studied in people with cancer, but mainly with quantitative studies. This study is the first to explore how adult cancer patients experience self-criticism and self-compassion in the context of their illness. Design: A multimethod qualitative study design was used, combining individual and group semi-structured interviews. Participants were 26 people with cancer who familiarized themselves with the topic by doing various self-compassion exercises for two weeks prior to the interview. Individual and group interviews were analyzed together using thematic analysis. Results: Four themes regarding self-criticism were identified: (1) being harsh or strict with yourself, (2) feeling guilty or angry, (3) feeling useless or like a burden, (4) feeling ashamed and not wanting to show weakness. Six themes regarding self-compassion were identified: (1) being mild to yourself, (2) guarding your boundaries, (3) accepting the illness and limitations, (4) maintaining a positive perspective, (5) connecting to others and (6) taking responsibility for your health. Conclusion: Our findings offer insights into practical and daily life experiences of self-criticism and self-compassion of people with cancer, which can aid the further development of theory, scales and interventions.